2020
DOI: 10.3390/v12121449
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous Transmission of West Nile Virus by a New Vector in Iran, Vector-Host Interaction Modeling and Virulence Gene Determinants

Abstract: Using molecular techniques and bioinformatics tools, we studied the vector-host interactions and the molecular epidemiology of West Nile virus (WNV) in western Iran. Mosquitoes were collected during 2017 and 2018. DNA typing assays were used to study vector-host interactions. Mosquitoes were screened by RT-PCR for the genomes of five virus families. WNV-positive samples were fully sequenced and evolutionary tree and molecular architecture were constructed by Geneious software and SWISS-MODEL workspace, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 66 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Despite the nationwide serological evidence on the prevalence of WNV since 1976 [27] and the establishment of Arbovirus monitoring system since 2000, there is a paucity of information about WNV vectors in Iran [29]. Also, the distribution map of the globally spreading Lineage 1a of West Nile Virus as a serious public health problem still not clear at national level [34]. The present study aimed to contribute towards WNV vectors identi cation and surveillance.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the nationwide serological evidence on the prevalence of WNV since 1976 [27] and the establishment of Arbovirus monitoring system since 2000, there is a paucity of information about WNV vectors in Iran [29]. Also, the distribution map of the globally spreading Lineage 1a of West Nile Virus as a serious public health problem still not clear at national level [34]. The present study aimed to contribute towards WNV vectors identi cation and surveillance.…”
Section: Discussionmentioning
confidence: 98%
“…pipiens pipiens and Cx. theileri in Iran [ 73 , 74 ] and 0.28% for Cx. nigripalpus in Chiapas, Mexico [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Shahhosseini et al identified WNV in Cx. theileri, one of the most common mosquito species in Iran, which suggests this may be a new vector for WNV within the country [107]. Furthermore, a recent study in southern Iran provided evidence that WNV can be transmitted vertically between female Culex mosquitoes and their offspring, which may explain how the virus survives the winter months.…”
Section: West Nile Virus Vector In Iranmentioning
confidence: 99%
“…Figure 2. Evidence of West Nile virus[48,96,99,107,[119][120][121][122], Chikungunya virus[15,[46][47][48], Dengue virus[15,48,58,60,62], Sindbis virus[75] and Rift valley fever virus[109] in Iran in either humans, animals, or mosquitoes by indirect and direct evidence.…”
mentioning
confidence: 99%